The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3855/jidc.5711
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and respiratory infections

Abstract: Vitamin D or 1,25-hydroxyvitamin D (1,25(OH) 2 D) has a well-established role in calcium homeostasis. In recent years, the discovery of vitamin D-metabolizing enzymes and vitamin D receptor (VDR) in the lungs and various cells of the immune system has led to numerous studies conducted to evaluate its role in respiratory functions and, in particular, upper respiratory tract infections (URTIs). A PubMed literature search was done using vitamin D and respiratory infections as key words. Only clinical studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
(92 reference statements)
0
10
0
3
Order By: Relevance
“…This could lead to increased exposure to viral and bacterial pathogens from the external environment, increasing the risk of URTIs. Li and Gleeson [131] have suggested that low vitamin D levels may exaggerate the vulnerability of athletes to URTIs, while individuals with higher vitamin D levels exhibit a lower propensity to URTI [132,133]. It has been suggested that vitamin D prevents the development of URTIs by affecting the activation of toll-like receptors (TLRs) [134].…”
Section: Effects Of Vitamin D On Immunitymentioning
confidence: 99%
“…This could lead to increased exposure to viral and bacterial pathogens from the external environment, increasing the risk of URTIs. Li and Gleeson [131] have suggested that low vitamin D levels may exaggerate the vulnerability of athletes to URTIs, while individuals with higher vitamin D levels exhibit a lower propensity to URTI [132,133]. It has been suggested that vitamin D prevents the development of URTIs by affecting the activation of toll-like receptors (TLRs) [134].…”
Section: Effects Of Vitamin D On Immunitymentioning
confidence: 99%
“…У сучасній літературі широко обговорюється роль вітаміну D (VD), а також значення його дефіциту в формуванні схильності дорослих та дітей до частих респіраторних захворювань [8,9]. Встановлення не щодавно факту активної участі VD в регуляції сис теми протиінфекційного імунітету та в забезпеченні ним функціонального балансу між Тлімфоцитами хелперами (Th) 1го типу і Th 2го типу [10]; можливос ті розвитку дисбалансу Th1/Th2 імунної відповіді в бік останніх за умов дефіциту VD, а також наявності під вищеної продукції протизапальних Th2асоційованих цитокінів [11] [14].…”
Section: вступunclassified
“…Vitamin D has a protective role against infections by stimulating the production of cathelicidin (antimicrobial peptide) and modulating the production of cytokines and the inflammatory cascade during the infection [40], so vitamin D deficiency has also been associated with an increased risk of infections, especially those of the respiratory tract, including tuberculosis [41].…”
Section: Vitamin D and Infectionsmentioning
confidence: 99%